The Influence of Growth Opportunity, Capital Structure, Dividend Policy on Firm Value in Agricultural Sector Companies in the Plantation Sub-Sector: Pengaruh Growth Opportunity, Struktur Modal, Kebijakan Dividen Terhadap Nilai Perusahaan pada Perusahaan Sektor Pertanian Sub Sektor Perkebunan - Setiyani, Ayu Fera; Hariasih, Misti (Indonesian Journal of Public Policy Review, 2020)
This study aims to examine the effect of growth opportunity, capital structure, dividend policy on firm value. The approach used in this research is a quantitative approach. The population in this study are plantation sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method. The sample in this study were 6 companies listed on the Indonesia Stock Exchange in 2015-2019. The data used in this study is secondary data taken from the Indonesia Stock Exchange. Data analysis uses Eviews 9 analysis with the aim of testing growth opportunity (X1), capital structure (X2) and dividend policy (X3) on firm value (Y). The results of this study indicate that there is a significant influence between growth opportunity, capital structure, dividend policy on firm value. Likewise, the variables of growth opportunity, capital structure, dividend policy have a simultaneous effect on firm value.